Addressing Adolescent Mental Health after Disasters: The Critical Role of Chronic Stressors. Issue Volume 34:Issue s1(2019) (May 2019) - Newnham, Elizabeth; Gao, Xue; Nathan, Elizabeth; Boyes, Mark; Jiao, Feng; Guragain, Bhushan; Leaning, Jennifer
Abstract : Introduction: Prolonged conditions of chronic stress have the potential to cause mental health difficulties and disrupt developmental processes for children and adolescents. Natural disasters disproportionately affect low-resource areas, yet little is known about the interaction between trauma exposure, chronic stressors, and mental health. Aim: To determine the rates of post-traumatic stress disorder (PTSD), depression and anxiety among adolescents affected by earthquakes in China and Nepal, and examine the specific roles of trauma exposure and chronic stressors across the three mental health outcomes. Methods: A school-based, cross-sectional study of 4, 215 adolescents (53% female, ages 15-19 years) was conducted in disaster-affected areas of southern China and Nepal. Participants completed a series of translated and culturally adapted standardized assessments. Mixed effects logistic regression analyses were conducted for each mental health outcome. Results: The overall rate of PTSD was 22.7% and was higher among Nepalese participants (China: 19.4% vs. Nepal: 26.8%, p<0.001), but did not differ between genders (China: p=0.087 and Nepal: p=0.758). In both countries, the level of trauma exposure was a significant risk factor for PTSD, depression, and anxiety (China: OR's 1.09-1.18 and Nepal: OR's 1.08-1.13). Chronic stressors significantly improved the model and further contributed to mental health outcomes (China: OR's 1.23-1.26 and Nepal: OR's 1.10-1.23). Multilevel risk and protective factors across all mental health outcomes will be presented. Discussion: While there are limited opportunities to protect adolescents from disaster exposure, there is significant potential to address the effects of ongoing economic insecurity, domestic violence, and school cessation that are likely to worsen mental health outcomes. Programs that identify chronic stressors for adolescents in disaster-affected settings, and work to address poverty and violence, will have cascading effects for mental health, development, and security.